1809: una guerra, un patriota y un plan de reforma de la educación pública - Nava Rodríguez, Teresa (Cuadernos de Historia Moderna, 2009)
Antonio Panadero, Lawyer of the Royal Councils, was in Madrid at the beginning of Spanish War of Independence and took part in acts of resistance against French occupation. However, he was not a man of arms, but of pen, and to it resorted, as a way to collaborate with the new authorities represented by the “Junta Suprema Central”, sending to them from his place of residence, it is, Miguel Esteban, several writings of pedagogical and political content. The work presented here has as main goal a partial transcription of one of those texts, the one called Sistema de Educación con arreglo al de reforma de la Constitución de España.